MINAT MAHASISWA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH STAIN AL-FATAH JAYAPURA UNTUK MEMPELAJARI KETERAMPILAN BERCERITA/MENDONGENG - Sigit Purwaka (MIDA : Jurnal Pendidikan Dasar Islam, 2019)
Abstract Students of Study Program Madrasah Ibtidaiyah Teacher Education as prospective class teachers in Madrasah Ibtidaiyah must have the skills to use various learning methods. One method of learning that requires special skills is the storytelling method. Storytelling is believed to have many advantages, especially in character inculcation. However, not all students are interested in learning storytelling skills and implementing them as learning methods.